Colonization of a Neotropical Reservoir (Córdoba, Argentina) by Ceratium hirundinella (O. F. Müller) Bergh - Mac Donagh, María Elicia (2005)
Blooms of Ceratium hirundinella (O. F. Müller) Bergh. have been detected in different water bodies in the Neotropical Region since 1990. The colonization began in southern lakes, and during the last decade the dinoflagellate arrived and bloomed in subtropical reservoirs. In this context the colonization of C. hirundinella and its population development have been analyzed from its first record in the Río Tercero Reservoir (February 1999 to February 2001). Phytoplankton and physicochemical samples were obtained from three sampling stations at the Reservoir, one in the outlet of the water cooling channel of the nuclear power plant, and one in the nearest tributary (Quillinzo River). Two blooms of C. hirundinella were detected during the warm seasons with temperatures higher than 18°C, and pH ranging between 8.5 and 8.9. Environmental conditions such as certain light intensity range and percentage of dissolved oxygen mentioned as favorable for Ceratium development were always recorded in Río Tercero Reservoir. Cysts were observed in spring and summer months. Another dinoflagellate (Peridinium gatunense Nygaard) bloomed in previous summer in this water body but its population density decreased during the invasive phase of colonization of C. hirundinella. Asplanchna girodi, became the dominant zooplankter after the first bloom of C. hirundinella. We believe that the presence of this dinoflagellate in the Neotropical Region could be a regional phenomenon associated with some dispersal mechanisms and favorable local conditions for its proliferation like those recorded in the Rio Tercero Reservoir